Stilistika dalam Puisi Karawang-Bekasi Karya Chairil Anwar : Kajian Gaya Bahasa dan Diksi - Mei Leani Olfah; Dwi Wahyu Candra Dewi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the language style and diction in the poem Karawang-Bekasi by Chairil Anwar using a stylistic approach. This poem is famous for its spirit of struggle that stirs up feelings of nationalism and the sacrifices of heroes. Through the analysis of language style, it was found that the use of figures of speech such as metaphor, personification, and hyperbole strengthen the emotional message of the poem. In addition, the diction chosen by Chairil Anwar has an important role in creating a heroic atmosphere and encouraging readers to absorb the meaning of the struggle. This study also reveals that the choice of words in this poem not only forms aesthetics, but also reflects a strong ideology of struggle. Thus, this finding enriches the understanding of the role of language style and diction in poetry as part of deep literary communication.